THE DYNAMICS MOLECULER OF WATER MOLECULE ABSORPTION IN SILICATE ZEOLITE - Nirwan Syarif (Institut Teknologi Bandung, 2007)
The water molecule dynamics absorbed at silicalite zeolite was studied with molecule dynamics technique using the computer. This paper reports the effect of temperature on behavior of dynamic system. The result showed the improvement of diffusion coefficient and diffusion activation energy along with the improvement of temperature. Improvement of temperature cause the change of the contact distance of the water molecule in zeolite molecule.